2017
DOI: 10.21595/jve.2017.18830
|View full text |Cite
|
Sign up to set email alerts
|

Research on pressure fluctuation characteristics of a centrifugal pump with guide vane

Abstract: In order to study the pressure pulsation characteristics of a centrifugal pump with a guide vane, a pump with specific speed = 190 was chosen as the research object. The numerical simulation was carried out using the standard-turbulence model. The pressure pulsation characteristic was researched at a set monitoring point. The reliability of the numerical simulation was verified with experiment results. The pressure pulsation characteristic curves of each calculation domain were obtained by dimensionless data p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Wang [4] took two-vane pump as the research object and applied particle swarm optimization algorithm to search and calculate the pump, and the hydraulic performance of the pump was improved after optimization. Wang [5] took guide vane centrifugal pump as the optimization objective and proposed an optimization method based on particle swarm optimization algorithm, which effectively improved the flow separation between guide vane and blade. Miao [6] adopted an optimization design method combining neural network and genetic algorithm in the optimization process of centrifugal pump blade profile, which effectively improved the pump operating efficiency at working conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Wang [4] took two-vane pump as the research object and applied particle swarm optimization algorithm to search and calculate the pump, and the hydraulic performance of the pump was improved after optimization. Wang [5] took guide vane centrifugal pump as the optimization objective and proposed an optimization method based on particle swarm optimization algorithm, which effectively improved the flow separation between guide vane and blade. Miao [6] adopted an optimization design method combining neural network and genetic algorithm in the optimization process of centrifugal pump blade profile, which effectively improved the pump operating efficiency at working conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Through CFD simulation, it is found that blade passing frequency and its higher harmonics dominate the downstream of impeller due to the rotor-stator interaction between impeller and guide vane or cut-water. [24][25][26] The corresponding strength of blade passing frequency is affected by the position of cut-water and the distance between impeller outlet and guide vane or cut-water (gap of vaneless region). 27,28 Current studies have shown that the gap of vaneless region changes due to eccentricity can affect rotor-stator interaction and the stability of flow.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang's method was more accurate in calculating the structural vibration caused by fluid excitation. Wang [14] calculated the pressure pulsation of the pump chamber, guide vane, impeller, and volute of a centrifugal pump via numerical calculations and compared the results with an experiment. He [15] established a finite element model of a pump unit including a motor.…”
Section: Introductionmentioning
confidence: 99%